A poem by Vlado Oláh (Východná, 1986): “Savore Roma le Gruskaske” - Viková, Lada; Andrš, Zbyněk (Romano džaniben, 2025)
This discovery report presents a previously unpublished poem by Vlado Oláh from 1986, found in the archives of Viliam Ján Gruska. The poem was written immediately after the premiere of the groundbreaking program Ľudia z rodu Rómov at the folklore festival in Východná and captures the powerful atmosphere of the Romani cultural revival of that time. The text is presented within a broader cultural-historical context, and the poem is analyzed as a significant document of Romani ethno-emancipation, collective identity, and solidarity among the Romani people in the second half of the 1980s, and is presented as a collective manifesto. A substantial part of the text is devoted to commemorating the figures who signed this poem, as well as mapping out the possible circumstances under which it was handed over to Viliam Ján Gruska.
Keywords: Vlado Oláh; Východná 1986; Ľudia z rodu Rómov; Romani literature; cultural emancipation; Gruska